Being Woman in the Land of Shari‘a: Politics of the Female Body, Piety, and Resistance in Langsa, Aceh - Muhammad Ansor (Al-Jami'ah: Journal of Islamic Studies, 2014)
This study investigates the dynamic of institutionalization of Shari’a in Aceh, which focuses on analysis of the patterns of Langsa women’s resistance against religious leaders and state interpretations of the dress standards in the public space. This matter emerged because the implementation of Shari’a has been supported by local people, but the standard of Islamic dress that should be applied is still debatable among various groups in Aceh that have varied understandings and different religious visions. The regulation of dress code has been an issue for religious leaders, intellectuals, and Moslem activists. The resistance of Langsa women against the politics of body discipline could be open and secret. To analyze the forms of women’s resistance, the researcher applied James C. Scott’s hidden transcripts theory. Inspired by this theoretical framework, the researcher found that Langsa women, intellectuals, and religious leaders expressed their resistance over how women should dress in public space. In collecting the data, the researcher used observation, in-depth interviews, and focus group discussions. Accordingly, the research shows how Langsa women express their resistance towards religious hegemony and state interpretation of Islam.[Tulisan ini membahas dinamika pelembagaan syariat Islam di Aceh dengan fokus resistensi tersembunyi perempuan Langsa terhadap penafsiran elite agama dan pemerintah perihal pembakuan standar pakaian di ruang publik. Meskipun implementasi syariat Islam Aceh mendapat dukungan masyarakat setempat, tetapi ketika sebuah tafsir tertentu tentang pakaian Islami dibakukan dalam regulasi (Qanun), muncul perdebatan dari sebagian muslim yang berpola pemikiran dan visi keagamaan berbeda. Bukan hanya perdebatan di kalangan elite agama, intelektual, maupun aktivis, perempuan di berbagai daerah di Aceh pun mengekspresikan resistensi, baik secara terbuka maupun tersembunyi. Peneliti menggunakan teori hidden transcripts sebagaimana dikemukakan James C. Scott untuk menganalisa resistensi tersebut. Data dikumpulkan melalui observasi, wawancara mendalam, serta diskusi kelompok terfokus (FGD). Penelitian ini memperlihatkan bagaimana perempuan Langsa mengekspresikan resistensi tersembunyi atas hegemoni elite agama dan pemerintah dalam menafsirkan Islam].